A Model of Online Teaching and Learning Policy Implementation Factors Affecting Success of Private Schools in Bangkok Metropolis (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research are as following:1)to study the factors of successful implementation of the policy; 2) to study the level of Teaching and Learning Policy Implementation Factors Affecting Success of Private Schools in Bangkok; 3) to study and examine a consistency of the online teaching models and learning practices which affect the success of private school in Bangkok with empirical data. This research was conducted through a mixed method through an interview, a group discussion, and a survey. The total number of 180 private school directors were included in the research.The results of the research show that1) There are 2 types of factors (internal factors and external factors) in regard to policy implementation of online teaching and learning management, affecting the success of private education institutions in Bangkok. The internal factors consist of standards and objectives, and policy resources. The external factors include 1) communication     2) law enforcement 3) social, economic and political environment 4) characteristics and competencies of operational units 5) leadership 6) operators’ attitudes, and 7) a success in implementing online instructional management policies2) Top 3 factors which affect an implementation of online teaching and learning management are1) leadership 2) standards and objectives, and 3) communication.3) The results of the study and examination about a consistency of the online teaching models are congruent with the empirical data (2/df = 0.81, GFI = 0.99, AGFI = 0.96 และ RMSEA = 0.0000)